Cubanness Within and Outside of Cuba - Mica Garrett (Revue LISA)
To define Cubanness inside and outside of Cuba is a difficult task. From Taínos to wave after wave of immigrants, Cubans have struggled with their identity. Whether under colonial rule or under a dictatorship, Cubans have been defined by others, forcing them to conform or be punished for it. Under Castro, the island’s dream of independence from Spanish colonial rule and American imperialism finally came true, but at a price. Many argue that there are two Cubas: the one that Castro would have us see, a romantic, idealized view of the Revolution, and the other side of Cuba that he and his followers deny. In addition, there is a very large Cuban constituency in the United States, including Mini Havana in Miami. There, Cubans have retained their language and culture, in part due to their resistance to assimilation and strong need to retain their identity as Cubans. In any case, Cuba is in transition and is slowly opening up to old ways of doing business, including tourism and private enterprise.